Influenza breakthrough infection in vaccinated mice is characterized by non-pathological lung eosinophilia - Chang, Lauren A.; Choi, Angela; Rathnasinghe, Raveen; Warang, Prajakta; Noureddine, Moataz; Jangra, Sonia; Chen, Yong; De Geest, Bruno G.; Schotsaert, Michael (Frontiers in Immunology, 2023)
Eosinophils are important mediators of mucosal tissue homeostasis, anti-helminth responses, and allergy. Lung eosinophilia has previously been linked to aberrant Type 2-skewed T cell responses to respiratory viral infection and may also be a consequence of vaccine-associated enhanced respiratory disease (VAERD), particularly in the case of respiratory syncytial virus (RSV) and the formalin-inactivated RSV vaccine. We previously reported a dose-dependent recruitment of eosinophils to the lungs of mice vaccinated with alum-adjuvanted trivalent inactivated influenza vaccine (TIV) following a sublethal, vaccine-matched H1N1 (A/New Caledonia/20/1999; NC99) influenza challenge. Given the differential role of eosinophil subset on immune function, we conducted the investigations herein to phenotype the lung eosinophils observed in our model of influenza breakthrough infection. Here, we demonstrate that eosinophil influx into the lungs of vaccinated mice is adjuvant- and sex-independent, and only present after vaccine-matched sublethal influenza challenge but not in mock-challenged mice. Furthermore, vaccinated and challenged mice had a compositional shift towards more inflammatory eosinophils (iEos) compared to resident eosinophils (rEos), resembling the shift observed in ovalbumin (OVA)-sensitized allergic control mice, however without any evidence of enhanced morbidity or aberrant inflammation in lung cytokine/chemokine signatures. Furthermore, we saw a lung eosinophil influx in the context of a vaccine-mismatched challenge. Additional layers of heterogeneity in the eosinophil compartment were observed via unsupervised clustering analysis of flow cytometry data. Our collective findings are a starting point for more in-depth phenotypic and functional characterization of lung eosinophil subsets in the context of vaccine- and infection-induced immunity.